Evaluating the effectiveness of CNN-based models for diabetic retinopathy detection - Niaz, H.M; Tajrian, Nuha; Alam, Mohammad Ahsan Ibn; Limon, Md. Shahriar Khan; Saha, Sharnit (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.